The LEGO book - Lipkowitz, Daniel (New York, New York DK Publishing, 2018)
"Discover the whole LEGO story and explore the incredible play themes, sets, minifigures, movies, and innovations. Celebrate the 60-year history of the iconic LEGO brick in this special updated and expanded edition of The LEGO Book"--
Hardcover may include commemorative LEGO brick
Includes index
1
Keywords: LEGO koncernen (Denmark); LEGO koncernen (Denmark) -- Juvenile literature; LEGO toys -- Juvenile literature; LEGO toys -- History -- Juvenile literature; LEGO toys; History